The Effect of RME Application on Mathematics Learning Outcomes - Aida Fitri Harun Pakpahan; Nur Halimah Matondang (International Journal of Educational and Psychological Sciences, 2023)
Student learning outcomes in mathematics learning are categorized as quite low, due to the lack of student participation in learning, so interesting learning methods are needed to improve student learning outcomes. The purpose of this study is to analyze students' mathematics learning outcomes after applying the Realistic Mathematics Education (RME) approach and explain the application of the Realistic Mathematics Education (RME) approach which has an impact on improving students' mathematics learning outcomes. This research uses literature studies as a data collection method. The source of data in this study amounted to 10 scientific articles accessed from several sites about the effect of applying the PMR approach on students' mathematics learning outcomes. Based on a review of several literature and scientific articles that have been accessed, the author concludes that the Realistic Mathematics Education (RME) approach has a positive impact on student learning outcomes. Realistic Mathematics Education (RME) can be a consideration for teachers to increase students' interest in learning so that their learning competence also increases, especially in the present.